(untitled) (Journal of Pharma Insights and Research, 2023)
The most prevalent non-communicable diseases that need long-term therapy include hypertension and diabetes mellitus. Mortality and morbidity rates increase when diabetes and hypertension are present together. These disorders must be taken into consideration in order to manage them successfully when they coexist. Both diabetes and hypertension are most likely to develop macrovascular and microvascular complications. Tight control of blood pressure is more helpful in diabetic-hypertensive patients than tight control of blood glucose levels. This study aims to learn about anti-diabetic and anti-hypertensive drug therapy, clinical outcomes, and how combination therapy affects the clinical outcome of diabetes with hypertension. It was a prospective single-centered observational study conducted among 300 Diabetic-Hypertensive patients. The mean age of the study was 58.8 years. According to this study, 56% were males and 44% were females. The commonly observed comorbidity conditions along with diabetes and hypertension were CKD (20.6%), UTI (15%), and Neuropathic diabetes (14%). The most affected occupations with diabetes and hypertension were Private Jobs (31%), Retired Employees (21%), and Homemakers (20%). The most prescribed drugs in diabetic-hypertensive patients were Metformin (7%), Metoprolol (11.7%), Metoprolol with Cilnidipine (5.6%), Metformin with Glimepiride (8.4%), Olmesartan with Amlodipine and Hydrochlorothiazide (8%), and Glimepiride with Metformin and Voglibose (6.3%). The conclusion of this study, males were more affected by diabetes and hypertension and mostly observed in the elderly. The anti-diabetic combination therapy and its clinical outcome are not associated with each other. The anti-hypertensive combination therapy and its clinical outcome are associated with each other